Efektivitas Konvergensi IFRS dalam Mengatasi Praktik Manajemen Laba di Indonesia - Suprianik; Dewi Rahmawati; Dinda Syevia Nazarina (PT. Gudang Pustaka Cendekia, 2024)
Earnings management practices that are increasingly common and have become a culture in some companies are one of the main problems in financial reporting. With the convergence of IFRS standards, it is expected that managers will produce high quality financial reports, so that reported earnings become more reliable. The purpose of this study is to analyze whether IFRS convergence that has been implemented in Indonesia is able to prevent earnings management practices in Indonesia. This research uses the literature study method, namely, secondary data obtained from articles related to IFRS convergence and earnings management practices in Indonesia. The results showed that the opportunity for earnings management practices still exists after convergence with IFRS, but the value of earnings management after IFRS convergence is lower than before the implementation of IFRS convergence.